Effects of dietary cecropin on growth performance, diarrhea rate and intestinal health of nursery Hainan pigs - Ouyang, Kun; Chen, Ting; Sun, Ruiping; Xie, Yali; Qi, Qi; Li, Xiang; Liu, Jie; Liu, Quanwei; Wei, Limin (Frontiers in Microbiology, 2024)
Antimicrobial peptides could inhibit the growth of harmful bacteria and promote the growth performance in weaned piglets. Here, we investigated the effects of dietary supplementation with cecropin antimicrobial peptides (CAP) on growth performance, diarrhea rate, intestinal health in nursery Hainan piglets.For this, one hundred and twenty healthy nursery Hainan male piglets (13.29 ± 0.29 kg, 44 days old) were randomly divided into 5 groups-a control (CON) group (fed a basal diet), an antibiotic control (AC) group (fed a basal diet supplemented with 250 mg/kg colistin sulfate); and 3 experimental groups (provided the basal diet supplemented with 250, 500, or 1,000 mg/kg CAP). Pre-feeding lasted 7 days and the official period lasted 40 days.The results showed that compared with the CON group, dietary supplementation of 500 mg/kg CAP had significantly increased the average daily gain (ADG, P < 0.05), while the feed conversion ratio (FCR) and diarrhea rate were markedly reduced (P < 0.05), serum total protein (TP), albumin, IgA, IgM, and globulin concentrations were significantly increased (P < 0.05), where serum aspartate aminotransferase (AST) level was significantly reduced (P < 0.05), and it also increased the villus height and the villus height-to-crypt depth ratio in the jejunum, reduced the serum D-lactic acid concentrations and diamine oxidase activity, and increased the expression level of ZO-1 and Occludin in the jejunum and ileum (P < 0.05), the relative abundance of Firmicutes, Lactobacillus, and Limoslactobacillus in the colon were increased (P < 0.05), whereas that of Streptococcus and Escherichia-Shigella were reduced (P < 0.05). Compared with the AC group, serum TP and globulin levels were significantly enhanced in the 500 mg/kg CAP group (P < 0.05).These results indicated that dietary supplementation with 500 mg/kg CAP could improve the growth performance, reduce the diarrhea rate, improve the serum immunity, intestinal health of nursery pigs.